Guo Xiang and the Problem of Self-Cultivation in Daoist Naturalism - Coles, Benjamin (Religions, 2019)
Recent research on Daoism has distinguished various models of self-cultivation present in the tradition, in particular those which aim at returning humanity to a natural, spontaneous form of existence (often associated with early pre-Qin "philosophical" Daoism), and those which aim at transcending human nature through technical practices (often associated with later "religious" Daoism). During the Wei-Jin period, organized Daoist religion was still in its early stages, yet the difference between the two models was very much an issue in the Dark Learning (xuanxue) thought of the intellectual elite. In this paper, I trace this debate as expressed in Wei-Jin thinker Guo Xiang's Commentary to the Zhuangzi, in particular in Guo's criticisms of the desire or attempt to exceed the limits (ji) of one's inherent nature and his reinterpretation of the Zhuangzi's criticisms of technical practices. While Guo follows Xiang Xiu in rejecting many of the claims of radical transcendence through self-cultivation, I argue that this does not imply that he lacks any positive conception of self-cultivation, but rather that he sees such cultivation as only possible through an immanent historical process in which both natural spontaneity and artificial techniques have a role to play.